Propaganda in International Relations : A Case Study of the Russian-Ukrainian Conflict - Kadlecová, Veronika (2015)
The thesis identifies and further examines the role of propaganda in the Russian-Ukrainian conflict, more specifically in the period around the annexation of the Crimean peninsula by the Russian Federation in March 2014. Critical discourse analysis is employed in order to analyse selected speeches of the President of the Russian Federation, Vladimir Putin, and the President of the United States of America, Barack Obama, relevant to the topic and in the period under investigation. The first chapter introduces a theoretical framework on propaganda in international relations, its definition, history and research. The methodology is described in detail in the second chapter. The historical context of the conflict is provided at the beginning of the empirical part of the thesis closely followed by a detailed analysis of the selected speeches. The findings support the prediction that there is a presence of propaganda identified within the speeches of both political leaders, thus in the conflict itself, and offer valuable insights into the hidden meanings and possible motives behind its use. The study advances our understanding of the phenomenon and helps us to expose and confront propaganda further.